Investigation of the UV-aging behavior of bio-based polyamides for automotive interiors - Tim Passinger; Lars Schmohl; Jan-Christoph Zarges; Julia Resch; Hans-Peter Heim; Christian Bonten (Polymer Testing)
Against the backdrop of limited fossil resources, bio-based plastics offer a sustainable and long-term solution. Polyamides made from bio-based raw materials (bio-PA) in particular is seen as a key driver for bio-based plastics. In the automotive industry in particular, engineering plastics such as PA are an important product group due to their material properties. Vehicle interiors, have to meet a variety of mechanical, optical and emission-related specifications set by the manufacturer and authorities. In order to enable the use of bio-based plastics in car interiors, it is therefore necessary that they meet the manufacturers' specifications. In this context, the bio-based PA510, PA610 and PA1010 were compared with those of the fossil-based PA6 after carrying out the UV-aging process standardized in DIN75220. In order to increase the resistance of the bio-based polyamides to UV-radiation, stabilization on a twin-screw extruder was carried out and the effect was characterized after another aging cycle. The results of FTIR spectroscopy and mechanical analysis indicate that UV aging has a strong effect on the bio-based PA, as an increase in absorption has occurred at certain wave numbers (1735 and 3080) and the tensile strength and elongation at break are significantly reduced. The use of a UV-stabilizer showed the potential to mitigate these effects to a considerable extent. In addition, the emission behavior of highly volatile substances according to VDA278 was determined using GC-MS and low-volatile substances according to DIN75201. The perceived odor impression was characterized with human testers in accordance with VDA270. The tests show very low emission values in the area of VOC and SVOC for all polyamides tested. All types are suitable for use in the passenger compartment. However, the determination of the perceived odor does not meet the limit value specifications for some types.